Groundwater quality evaluation using Water Quality Index and GIS technique for the Holocene and Pleistocene aquifers in the coastal zone of Ninh Thuan province - Trinh Hoai, Thu; Tran Thi, Thuy Huong; Le Thi , Phuong Quynh; Vu Le , Phuong; Le Duc, Anh; Mai Duc , Dong (Vietnam Journal of Marine Science and Technology, 2021)
This study represents the application of the Water Quality Indices (WQI) and GIS techniques to grading water pollution and the factors that influenced the groundwater quality of the Holocene (qh) and Pleistocene (qp) aquifers in the coastal zone of Ninh Thuan province. 100 underground water samples were collected from residential water well of qh aquifer (53 samples) and qp aquifer (47 samples). Water quality indices using in the study incorporated total dissolved solids (TDS), chloride (Cl-), flouride (F-), nitrite (NO2-), nitrate (NO3-), iron (Fe3+), manganese (Mn2+). Calculated WQI grading scale for the groundwater quality of the 100 water samples ranged from very good to inedible for drinking purpose. The result shown the water sample graded as “excellent water quality” accounted the most (23,3% and 14,9% for the qh and qp aquifer, respectively), the followings were “good water quality” grade ranked the second (9,4% and 8,5%); “poor water quality” grade (43,4% and 30,04%); “very poor water quality” grade (1,89% and 10,64%); and “inedible” grade (16,98% and 31,9%). Water samples graded as “very poor” and “inedible” were mostly distributed on the southeast of Ninh Hai district and Tri Hai commune (Ninh Hai district), Xuan Hai and Cong Hai communes (Thuan Bac district), Phuoc Thuan (Ninh Phuoc district) of the qh aquifer, and to the south of study area of the qp aquifer because of the exceptionally high TDS. Other samples which were low on TDS but graded “bad” due to surprisingly high concentrations of other ions (Cl-, NO3-, NO2-). The result provided concreted information on the polluted agents in groundwater and a valuable tool to support authorities in management and zoning groundwater quality of the study area.